Π-Helix controls activity of oxygen-sensing diguanylate cyclases. Issue 2 (20th February 2020) - Walker, Johnnie A.; Wu, Yuqi; Potter, Jacob R.; Weinert, Emily E.
Abstract: The ability of organisms to sense and adapt to oxygen levels in their environment leads to changes in cellular phenotypes, including biofilm formation and virulence. Globin coupled sensors (GCSs) are a family of heme proteins that regulate diverse functions in response to O2 levels, including modulating synthesis of cyclic dimeric guanosine monophosphate (c-di-GMP), a bacterial second messenger that regulates biofilm formation. While GCS proteins have been demonstrated to regulate O2 -dependent pathways, the mechanism by which the O2 binding event is transmitted from the globin domain to the cyclase domain is unknown. Using chemical cross-linking and subsequent liquid chromatography-tandem mass spectrometry, diguanylate cyclase (DGC)-containing GCS proteins from Bordetella pertussis ( Bpe GReg) and Pectobacterium carotovorum ( Pcc GCS) have been demonstrated to form direct interactions between the globin domain and a middle domain π-helix. Additionally, mutation of the π-helix caused major changes in oligomerization and loss of DGC activity. Furthermore, results from assays with isolated globin and DGC domains found that DGC activity is affected by the cognate globin domain, indicating unique interactions between output domain and cognate globin sensor. Based on these studies a compact GCS structure, which depends on the middle domain π-helix for orienting the three domains, is needed for DGC activity and allows for direct sensor domain interactions with both middle and output domains to transmit the O2 binding signal. The insights from the present study improve our understanding of DGC regulation and provide insight into GCS signaling that may lead to the ability to rationally control O2 -dependent GCS activity.